2003
DOI: 10.1073/pnas.0537849100
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to a cannabinoid agonist produces memory deficits linked to dysfunction in hippocampal long-term potentiation and glutamate release

Abstract: To investigate the possible long-term consequences of gestational exposure to cannabinoids on cognitive functions, pregnant rats were administered with the CB1 receptor agonist WIN 55,212-2 (WIN), at a dose (0.5 mg͞kg) that causes neither malformations nor overt signs of toxicity. Prenatal WIN exposure induced a disruption of memory retention in 40-and 80-day-old offspring subjected to a passive avoidance task. A hyperactive behavior at the ages of 12 and 40 days was also found. The memory impairment caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
153
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 37 publications
11
153
3
3
Order By: Relevance
“…However, interfering with the delicate balance of eCB signaling even with low concentrations of ⌬ 9 -THC during embryogenesis triggered aberrant patterning of CCK͞ CB 1 R-expressing interneurons in the early postnatal hippocampus. The notion that ⌬ 9 -THC significantly affects this principal subset of perisomatic inhibitory basket cells (38) suggests that an altered inhibitory drive on pyramidal cells triggers discordant excitatory output from hippocampal neuronal circuitries (2,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, interfering with the delicate balance of eCB signaling even with low concentrations of ⌬ 9 -THC during embryogenesis triggered aberrant patterning of CCK͞ CB 1 R-expressing interneurons in the early postnatal hippocampus. The notion that ⌬ 9 -THC significantly affects this principal subset of perisomatic inhibitory basket cells (38) suggests that an altered inhibitory drive on pyramidal cells triggers discordant excitatory output from hippocampal neuronal circuitries (2,10).…”
Section: Discussionmentioning
confidence: 99%
“…A coincidence of eCB synthesis and release and CB 1 R activation within axonal growth cones was postulated to provide an eCB-driven reinforcement loop that regulates axonal growth and guidance (8). Although the functional significance of CB 1 Rs during assembly of cortical neuronal circuitries is unknown, their developmental impact is illustrated by long-lasting cognitive, motor, and social disturbances in offspring exposed prenatally to cannabis (9,10).…”
mentioning
confidence: 99%
“…Developmental THC administration induces alterations in synaptic connectivity and plasticity (18,19), but its long-lasting functional consequences remain largely unknown. Therefore, we analyzed whether seizure susceptibility was affected in the adult offspring of THC-administered pregnant mice by using a pentylenetetrazole (PTZ) administration paradigm.…”
Section: Prenatal Thc Exposure Induces Long-lasting Alterations In Skmentioning
confidence: 99%
“…Another crucial clue came from HTLV-1 envelope binding studies, which suggested that the receptor was expressed very early after lymphocyte activation, and that its temporal pattern of expression was distinct from that of many other activation markers 4,5 . Together, these clues led the authors to GLUT-1, a member of a family of glucose transport proteins.…”
Section: Htlv-1 Infection Poses a Risk For Leukemia And Other Ailmentmentioning
confidence: 99%
“…The active constituent of marijuana, ∆ 9 -tetrahydrocannabinol (THC), binds to most nerve cells and some immune cells. Prenatal exposure of rats and mice to chemicals that engage these receptors reduces birth weight and impairs exploratory behavior and memory in offspring 3,4 .…”
mentioning
confidence: 99%